Business. (Economist, 2011)
The article offers world business news briefs in August 2011. U.S. Secretary of the Treasury Timothy Geithner has announced he plans on staying on as Treasury secretary. Kraft Foods mentioned it is splitting its business into two independent public companies, one focused on North American grocery products and the second on its global snack food brands. Computer hackers attached the Hong Kong stock exchange website, resulting in the exchange suspending trade in the shares of seven companies.